2015
DOI: 10.1016/j.jaci.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ligands for Siglec-8 and Siglec-9 in human airways and airway cells

Abstract: Background Balanced activation and inhibition of the immune system ensures pathogen clearance while avoiding hyperinflammation. Siglecs, sialic acid binding proteins found on subsets of immune cells, often inhibit inflammation: Siglec-8 on eosinophils and Siglec-9 on neutrophils engage sialoglycan ligands on airways to diminish ongoing inflammation. The identities of human siglec ligands and their expression during inflammation are largely unknown. Objective The histological distribution, expression and mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 44 publications
2
54
0
2
Order By: Relevance
“…Supporting this notion, an ex vivo study showed that eosinophils isolated from the brochoalveolar fluid of allergen-challenged patients have increased susceptibility to Siglec-8-mediated apoptosis (16). Immunohistochemical analysis consistently revealed that endogenous Siglec-8 ligands are markedly up-regulated in inflamed compared with normal human airway tissues (17). Collectively, these findings led to the proposal that Siglec-8 may provide a safeguard mechanism for the immune system to selectively deplete eosinophils from inflamed tissues and simultaneously diminish mast cell inflammatory responses and may thus constitute a basic immunoregulatory pathway to trigger the active resolution of inflammation and return to homeostasis (7,18) (Fig.…”
Section: Significancementioning
confidence: 91%
“…Supporting this notion, an ex vivo study showed that eosinophils isolated from the brochoalveolar fluid of allergen-challenged patients have increased susceptibility to Siglec-8-mediated apoptosis (16). Immunohistochemical analysis consistently revealed that endogenous Siglec-8 ligands are markedly up-regulated in inflamed compared with normal human airway tissues (17). Collectively, these findings led to the proposal that Siglec-8 may provide a safeguard mechanism for the immune system to selectively deplete eosinophils from inflamed tissues and simultaneously diminish mast cell inflammatory responses and may thus constitute a basic immunoregulatory pathway to trigger the active resolution of inflammation and return to homeostasis (7,18) (Fig.…”
Section: Significancementioning
confidence: 91%
“…Similarly, human Siglec-9 ligands have been shown to participate in inflammation. In a study of patients with chronic rhinosinusitis, Jia et al [74] demonstrated that Siglec-9 ligands were significantly upregulated in a subset of submucosal gland cells, epithelium, and connective tissue of the inferior turbinate. Upregulation of Siglec-9 ligands could, in turn, elevate the expression of mucin 5B in an NF-κB-dependent pathway.…”
Section: Natural Ligands For Siglec-9 and Siglec-ementioning
confidence: 99%
“…Siglecs predominantly bind to sialic acids on cell surface proteins (17), and play an important role in the internalization of sialic acid-expressing pathogens (1820), in controlling allergic asthma (21, 22), and in self-tolerance (23). Previously, we found that interaction between CD24 and SiglecG/10 is a key regulator of polybacterial sepsis, and this interaction requires sialylation of CD24 (24, 25).…”
Section: Introductionmentioning
confidence: 99%